Late Holocene vegetation and climate changes in the Great Hinggan Mountains, northeast China. (10th November 2019) - Han, Dongxue; Gao, Chuanyu; Yu, Zicheng; Yu, Xiaofei; Li, Yunhui; Cong, Jinxin; Wang, Guoping
Abstract: High-latitude region is sensitive to global climate change, and pollen record in sediments could reflect vegetation variation which responded to climate change. The Great Hinggan Mountains are main distribution areas of peatlands in high-latitude region in China and located at East Asian summer monsoonal margin, however, the variation of vegetation and climate in this region is still unclear. Based on the AMS 14 C dating, we analyzed the pollen assemblages to reconstruct vegetation history in Tuqiang (TQ) peatland, and we also used the principal component analysis to reconstruct the temperature and effective moisture and compared with other palaeoclimate records. Pollen assemblage denoted a coniferous and broad-leaved mixed forest on the surrounding mountains, and peatland vegetation gradually evolved from herb community (Cyperaceae) to bush community (Ericaceae). The climate of north part in the Great Hinggan Mountains was mainly controlled by the East Asian Summer Monsoon which related to ocean-atmosphere interactions in the tropical Pacific. During the period from 3300 to 1150 cal yr BP, the dominant plant was Cyperaceae, with coniferous and broad-leaved mixed forests bordered the peatland, which pointed to a relatively warm and wet climate. Between 1150 and 600 cal yr BP, the expansion of pine forests indicated a cool climate. The interval of 600–300 cal yr BP, the climate became cold and dry which related to the Little Ice Age. Since the 300 cal yr BP, Betula and Ericaceae dominated, the climate became warmer and drier. The obvious increase of secondary birch forests at the expense of pine forests may be the results of human disturbance, anthropogenic activities strengthened gradually and the variation of peatland vegetation was influenced mainly by anthropogenic activities rather than by climate since approximately 600 cal yr BP.